Evaluación técnico financiera para rediseño del fluido base sintética en perforaciones exploratorias de aguas profundas de la Cuenca del Sinú Costa Afuera (2017)
A technical and financial evaluation was carried out for the redesign of a synthetic base drilling fluid. This study was carried out in deepwater exploratory drillings of the Sinú Costa Afuera Basin for the conduct sections (Riser). For this, the geological generalities of the basin were studied, such as: history, location, stratigraphy, the main characteristics of the formations; history of production and the conditions and risks involved in drilling a well with a reduced operating window; drastic changes that experience certain properties between the surface, the seabed and the target; and the specific properties of different compounds or additives to improve the drilling fluid so that it satisfactorily meets all the challenges it faces and thus perform the drilling operation with the greatest possible success.